2013
DOI: 10.1056/nejmoa1311388
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Genotype-Guided Dosing of Acenocoumarol and Phenprocoumon

Abstract: Genotype-guided dosing of acenocoumarol or phenprocoumon did not improve the percentage of time in the therapeutic INR range during the 12 weeks after the initiation of therapy. (Funded by the European Commission Seventh Framework Programme and others; EU-PACT ClinicalTrials.gov numbers, NCT01119261 and NCT01119274.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
195
1
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(212 citation statements)
references
References 18 publications
5
195
1
9
Order By: Relevance
“…Using non-profit website published algorithm http: //www.WarfarinDosing.org., we assessed initial pharmacogenetically-predicted warfarin dose, introducing a loading-dose strategy of warfarin for each patient in PhG during the first two to five days, while subsequently patients were treated on the basis of the INR (28)(29)(30). In the control group, warfarin was introduced by a fixed dose of 2 tablets of 3 mg warfarin (6 mg) for the first two to five days, and the doses …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using non-profit website published algorithm http: //www.WarfarinDosing.org., we assessed initial pharmacogenetically-predicted warfarin dose, introducing a loading-dose strategy of warfarin for each patient in PhG during the first two to five days, while subsequently patients were treated on the basis of the INR (28)(29)(30). In the control group, warfarin was introduced by a fixed dose of 2 tablets of 3 mg warfarin (6 mg) for the first two to five days, and the doses …”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Pirmohamed group (EU-PACT trial) found that pharmacogenetic-based dosing was associated with a higher percentage of time in the therapeutic INR range than standard dosing during the initiation of warfarin therapy (27), while Kimmel group (COAG trial) did not confirm these findings for the anticoagulation period of the first 4 weeks of warfarin therapy (28). Also, Verhoef group did not confirm the findings for acenocoumarol or phenprocoumon during 12 weeks after the initiation of therapy in patients with atrial fibrillation or venous thromboembolism (29).…”
Section: Introductionmentioning
confidence: 97%
“…Kreatinin klerensi <30 mL/dk altında olan kişilerde ciltaltı fondaparinuks kontraendikedir ve orta derecede böbrek yetersizliğinde (kreatinin klerensi 30-50 mL/dk) dozu %50 azaltılmalıdır 24 . 27 .…”
Section: Parenteral Antikoagülasyonunclassified
“…L'étude conclut qu'inté-grer l'information génétique ne permet pas de mieux contrôler le dosage de warfarine au cours des quatre premières semaines de traitement. La seconde étude [22], portant sur 548 patients traités avec deux autres anticoagulants proches de la warfarine, l'acénocou-marol et le phenprocoumone, conclut également à l'absence d'amélioration du contrôle des doses au bout de 12 semaines de traitement, selon que la dose initiale est fixée par un algorithme intégrant des données que des différences de taux de concordance entre paires de jumeaux monozygotes et dizygotes, est considérée aujourd'hui comme bien décrite. Depuis l'identification d'un premier gène impliqué dans la susceptibilité à la maladie par l'équipe de Jean-Pierre Hugot en 2001 [12], la liste n'a cessé de s'allonger.…”
Section: L'exemple De La Maladie De Crohnunclassified